2021
DOI: 10.3389/fcell.2021.638815
|View full text |Cite
|
Sign up to set email alerts
|

LHPP-Mediated Histidine Dephosphorylation Suppresses the Self-Renewal of Mouse Embryonic Stem Cells

Abstract: Self-renewal of embryonic stem cells (ESCs) is orchestrated by a vast number of genes at the transcriptional and translational levels. However, the molecular mechanisms of post-translational regulatory factors in ESC self-renewal remain unclear. Histidine phosphorylation, also known as hidden phosphorylation, cannot be detected by conventional experimental methods. A recent study defined phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) as a histidine phosphatase, which regulates variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…Thus, we decided to detect histidine phosphorylation levels following LHPP expression alteration in GC cells. Consistent with previous reports 17 , fewer 1-pHis proteins were detected compared with 3-pHis proteins. However, our data indicated that the enzymatic active site of LHPP is neither the cysteine residue at position 226 nor at position 53 in GC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, we decided to detect histidine phosphorylation levels following LHPP expression alteration in GC cells. Consistent with previous reports 17 , fewer 1-pHis proteins were detected compared with 3-pHis proteins. However, our data indicated that the enzymatic active site of LHPP is neither the cysteine residue at position 226 nor at position 53 in GC.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, neither the an-oncogenic effect of LHPP nor the PI3K/AKT/mTOR pathway was not been disrupted with LHPP site mutation (Figure 5C-G). Inconsistent with previous articles [2,17], our data revealed that the enzymatic active site of LHPP may not be present in the cysteine residues at positions 53 and 226.…”
Section: The Enzymatic Active Site Exploration Of Lhppsupporting
confidence: 86%
See 1 more Smart Citation
“…Mechanistically, LHPP suppresses cancer cell proliferation, metastasis, and energy metabolism and promote cell apoptosis and autophagy. Interestingly, Xia et al illustrated [ 31 ] that LHPP -mediated histidine dephosphorylation repressed self-renewal of mouse embryonic stem cells by mediating the mRNA or protein expression of β-catenin, CDK4 and CyclinD1. Therefore, we chose to explore LHPP functions systematically, in addition to other molecular features and genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, as a kind of histidine phosphatase with homodimerization and diphosphatase activity, the LHPP protein is mainly correlated with substance metabolism, which has been proved in colitis, hepatocellular carcinoma [ 5 ] and embryonic stem cells [ 31 ]. Additionally, the dephosphorylation function of LHPP protein has been also widely studied in multiple cancers.…”
Section: Discussionmentioning
confidence: 99%